Apollo and the moon landing - Vogt, Gregory (Vogt, Gregory. Missions in space., 1991)
Traces the efforts of the United States to put a man on the moon, from President Kennedy's historic prediction in 1961 through the completion of the Apollo 17 mission in 1972.